NEW PRODUCT COMMERCIALIZATION STRATEGY ASSESSMENT WITH MCDM-BASED IN LCD DISPLAY COMPANY - Meng-Jong Kuan, Yee Ming Chen (International Journal of Research Science and Management, 2014)
This work presents results from a research developed in a TFT LCD display company. The main objective of this research was to assess new product commercialization strategy. Commercialization performance assessment is a Multiple Criteria Decision Making (MCDM) problem. A framework is proposed and uses a novel hybrid MCDM model to address the dependence relationships of criteria with the aid of the Decision-Making Trial and Evaluation Laboratory (DEMATEL), analytical network process (ANP) and VIKOR (VlseKriterijumska Optimizacija I Kompromisno Resenje). In order to show the practicality and usefulness of this framework, an empirical study of the Taiwan TFT LCD display company is demonstrated. The results of this study should provide a base for firms in evaluating the commercialization strategy which criteria provide the most effective direction towards improvement.